Biocompatibility and biocidal effects of modified polylactide composites - Stachurová, Tereza; Rybková, Zuzana; Škrlová, Kateřina; Malachová, Kateřina; Havlíček, Miroslav; Plachá, Daniela (Frontiers in Microbiology, 2022)
Polylactide materials treated with antimicrobial fillers represent a suitable alternative to the production of medical devices. Their advantage is that they can prevent the growth of microorganisms and the formation of microbial biofilms on the surface and around composites. The work is focused on the evaluation of biocompatibility and biocide effect of polylactide composite films filled with vermiculite and graphene oxide modified with silver (Ag+ and Ag nanoparticles), hexadecylpyridinium and hexadecyltrimethylammonium cations and their degradation leachates monitored at 1-3-6-month intervals. The antimicrobial effect of the leachates was detected by microdilution methods on gram-negative (Escherichia coli, Pseudomonas aeruginosa, Proteus mirabilis), gram-positive (Staphylococcus aureus, Streptococcus salivarius) bacteria and yeast (Candida albicans). The biocidal effect of composites on biofilm formation on the surface of composites was monitored by Christensen method and autoaggregation and motility tests. The biocompatibility of the composite and the leachates was assessed by MTT cytotoxicity assay. The evaluation of the antimicrobial effect of the leachates demonstrated that leachates of polylactide composite filled with graphene oxide and Ag+ showed a stronger antimicrobial effect than leachates of polylactide composite filled with vermiculite and Ag+ and Ag nanoparticles. The leachates of polylactide composites containing vermiculite with hexadecylpyridinium and hexadecyltrimethylammonium cations had a higher antimicrobial effect on G+ bacteria and yeast than G- bacteria. Bacterial growth, biofilm formation, autoaggregation and motility of the tested bacteria were most inhibited by the composite with vermiculite and Ag+ and Ag nanoparticles. Even after a 6-month degradation of this composite, bacterial growth and biofilm formation continued to be strongly inhibited up to 42% and 91%, respectively. The cytotoxic effect was proved only in the leachate of the composite with vermiculite containing hexadecylpyridinium after six months of its degradation. Tests evaluating the biocompatibility of materials have shown that the vermiculite is the most preferred carrier and can be used in the future to bind other compounds. The study confirmed that polylactide composite filled with vermiculite and Ag+ and Ag nanoparticles was the most stable and effective composite with the best biocompatible and biocidal properties.